Effect of Extraction Systems of Cannabinoid From Cannabis Sp on TLCDensitometric Chromatogram Pattern - N.M.P. Susanti; I M.A.G.Wirasuta; I N. K. Widjaja; K.W. Astuti; N.L.P.V. Paramita (Pharmacy Department, Math and Sciences Faculty, Udayana Univerity, 2012)
Optimization studies of cannabinoid extraction method of Cannabis sp have been conducted. The aim of this study was to find a marijuana extraction method to identify cannabinoid compounds using TLC–Spectrophotodensitometry technique. This study covers the process of maceration and soxhlet extraction to extract cannabinoid content in marijuana flowers and seeds using methanol PE, and ether as a solvent, followed by a screening test using the TLC- Spectrophotodensitometry method. Confirmation test used Fast Blue B salt to visualize color of the spots. CBN, THC, and CBD can be separated by either using the stationary phase of Al-TLC SI G60 F254 with a mobile phase of hexane - diethylether with the color visualization and Rf value after spraying with Fast Blue B Salt are the CBN will provide the purple-pink color with the HRF 59, THC will provide the purple color with the HRF 66, and the CBD will give orange color with the HRF 73 [1,2]. These results indicate that CBN, THC and CBD can be separated by either using the Al-TLC SI G60 F254 system with a mobile phase of hexanediethylether (80: 20, v / v). Differences in extraction methods affect the pattern of TLCDensitometry chromatogram peak. This effect on the profiling of simplicia. Keywords: Extraction; Cannabinoid; Al-TLC; Spectrophotodensitometry